2008
DOI: 10.1007/s00776-008-1242-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric exercise on the healing process of injured patellar tendon in rats

Abstract: Background. Earlier studies have reported positive results from eccentric training in patients with tendon disorders. The reasons for the benefi cial clinical effects of eccentric training are not known. Vascularization followed by regression of the vasculature enhances the healing response of injured tendons. Eccentric exercise induces a more benefi cial healing response than concentric exercise. Methods. Sixty rats with patellar tendon injuries were divided into three groups: nonexercise controls (group N; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…Changes in tendon vascularization have also been accounted for by others as partially an adaptation to exercise, which is induced by an increased VEGF expression (Gavin and Wagner, 2001;Pufe et al, 2005;Nakamura et al, 2008). As MMP-2 activity is frequently associated with the process of angiogenesis in several tissues (Lafleur et al, 2003;Rundhaug, 2005), the activation of MMP-2 after exercise observed herein may also be related to changes in blood vessel volume fraction at peritendinous sheath.…”
Section: Discussionsupporting
confidence: 51%
“…Changes in tendon vascularization have also been accounted for by others as partially an adaptation to exercise, which is induced by an increased VEGF expression (Gavin and Wagner, 2001;Pufe et al, 2005;Nakamura et al, 2008). As MMP-2 activity is frequently associated with the process of angiogenesis in several tissues (Lafleur et al, 2003;Rundhaug, 2005), the activation of MMP-2 after exercise observed herein may also be related to changes in blood vessel volume fraction at peritendinous sheath.…”
Section: Discussionsupporting
confidence: 51%
“…The efficacy of laser therapy on the behavior of angiogenesis had already been mentioned by Lins et al (2010), who reviewed the biostimulation effects of low-level laser on the tissue repair process. However, during this process, increased vascularity is initially expected, which should be followed by a subsequent reduction (Nakamura et al 2008). This was exactly what occurred in animals that had been treated only with laser therapy.…”
Section: Discussionmentioning
confidence: 95%
“…According to Orhan et al (2004), the appearance of adhesions depends on the degree of mobilization of the tendon during the healing period. With regard to the controlled physical activity, Nakamura et al (2008) reported that physical exercise is essential for the recovery of the tendon, since it contributes to the realignment of tendon fibers. Additionally, it has been demonstrated that the immobilization of the limb may affect the biomechanical properties of the tendon (Wren et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations